Juridical Implications of the Constitutional Court Decision Number 150/PUU-XXII/2024 on Legal Aid Provision in Indonesia - Yuda Hanafi Lubis; Cahya Wulandari (Universitas Negeri Semarang, 2025)
The provision of legal aid is a crucial aspect of law enforcement and access to justice, especially for underprivileged communities. However, the limited number of advocates and their uneven distribution has hindered the effectiveness of legal aid. One potential solution is involving civil servant lecturers (PNS) as advocates, although this was previously obstructed by the provisions in Law Number 18 of 2003 concerning Advocates. The Constitutional Court Decision Number 150/PUU-XXII/2024 granted legal standing for PNS lecturers to become advocates and participate in providing legal aid. This study, using a normative juridical method with a qualitative approach, found significant legal implications, such as the conditional unconstitutionality of two articles in the Advocate Law, the expansion of the definition of “advocate,” and the recognition of PNS lecturers, including government-contracted lecturers (PPPK), as eligible to represent clients in court. Previously, ASN lecturers were restricted from litigating and lacked technical regulations to support such roles. Following this decision, there is a need to harmonize regulations, establish ethical oversight bodies, expand lecturers' community service roles, improve teaching quality, and manage potential conflicts of interest. This study recommends revising the Advocate Law, issuing implementing regulations, strengthening university institutional frameworks, enhancing ministry-level oversight, and conducting public outreach on lecturers’ new role in expanding access to justice.